Pemerolehan Morfosintaksis Bahasa Melayu Palembang : Studi Kasus pada Anak Usia 2 Tahun 8 Bulan - Emawati (Medan Resource Center, 2022)
The purpose of this study was to describe in depth the acquisition of the Palembang Malay language, especiallythe morphosyntactic acquisition of children aged two years and eight months. Data analysis technique used in this study was the agih and matching method. The agih method was used to describe the morphosyntactic elements produced by the research participants. Furthermore, the equivalent method is used to analyze things that are out of the language focus. Therefore, the most suitable technique to use was the referential sorting technique. Thistechnique was used to see the relationship between the acquisition of Palembang Malay morphosyntax with the use of language at home, community, and school environment. The results showed that the acquisition of Palembang Malay morphosyntax in children aged two years and eight months developed very rapidly. Children are able to master and understand the meaning of the words and sentences they produce, even if those words were only in the form of simple sentences. Monomorphemic and polymorphemic forms have been used and mastered bychildren at the age of two years and eight months. Furthermore, children have acquired the syntax, interrogative, imperative and negative forms of language and have controlled them, although only simple sentences are producedby children.